Evaluation of young pigs of different genotypes by breeding indexes and growth indicators - Sukhno, T. (Scientific Progress & Innovations, 2024)
The article examines the influence of the interaction between the genotype of the DNA marker of the melanocortin 4 gene and the level of feeding of young pigs on its growth and development. The purpose of the work is to determine the breeding value of young pigs with different genotypes according to the DNA marker of the melanocortin 4 receptor gene under different types of feeding. To achieve the goal, the following tasks were performed: typing of young breeding pigs was carried out according to the MC4R marker; indicators of the age of reaching 100 kg live weight, average daily gains, relative gains and fat thickness at the level of the 6-7 thoracic vertebra were investigated, the experimental young pigs were evaluated using selection indices and the indicators of the intensity of formation, growth tension and uniformity of growth indices were calculated. For genetic studies, 50 blood samples were taken from F1 pigs of a two-breed combination (Large White × Landrace), pigs of experimental groups with an increased level of feeding received 10 % more energy and 12 % more crude protein in their daily diet. It was found that the feeding factor has a significant effect on the age at which experimental pigs reach 100 kg live weight (F=7.04; p=0.011). A significant influence of both the feeding factor (F=11.97; p=0.001) and the interaction of two organized factors: genotype and feeding (F=7.96; p=0.007) was established. According to the selection index of Berezovsky, a significant influence of each studied factor was recorded separately (feeding – F=5.80, p=0.02; genotype – F=12.85, p=0.001) and their interaction (F=8.56, p=0.005). A significant influence of the genotype of experimental pigs was established on Tyler's breeding index (F=22.31, p<0.001). Moreover, the best results were recorded in the group of pigs with the GG genotype that received an increased diet. Their advantage over counterparts with the GA genotype amounted to 6.6 units, or 4.34 % (p=0.015), and over pigs with the GA genotype that received a limited diet – 9.2 units, or 6.12 % (p=0.001). It was established that the average daily growth of young breeding animals at the age of 2 to 6 months is reliably influenced by the interaction of genetic factors with the level of feeding (F=7.96; p=0.007), which indicates the feasibility of adjusting rations depending on the genotype by DNA marker MC4R c.1426 G>A SNP. Indices of tension and uniformity of growth were the lowest in the group of pigs with the MC4R GA genotype under normalized feeding. This group was also distinguished by the lowest average daily gains and the worst values of selection indices, which may indicate the expediency of using indicators of tension and uniformity of growth for pre-selection of the best animals at the stage of early ontogenesis.